The Influence of Family Social Support on Resilience of Adolescent Children of International Migrant Workers - Sundayani, Yana; Nurwati, R. Nunung; Rusyidi, Binahayati; Fahrudin, Adi (Journal of Ecohumanism, 2024)
The study aims to examine how much influence family social support has on the resilience of adolescent children of international migrant workers. This research is based on social ecology theory covering micro, mezo and macro levels from Zastrow, 2017. The research design used a survey, with data collection tools using a questionnaire. The sample is adolescents aged 13 to less than 18 years whose mothers are international migrant workers from areas randomly selected by cluster random sampling. Data collection instruments used Davidson's (2018) Resilience Scale to measure resilience and Bernal's (2003) Cuestinario de Apoyo Social to measure family social support. The analysis used multiple linear regression with the Statistical Package for Social Sciences version 25 (SPSS 25) application tool to test associations. The study was conducted in 5 (five) village areas of Juntinyuat Sub-district, Indramayu Regency, West Java, Indonesia. The respondent 150 adolescent boys and girls with an average age of 16 years participated in the study. Respondents' mothers on average worked for more than 2 (two) years as migrant workers in Asia and the Middle East. Descriptive data showed that the average level of resilience was in the high category, 44% male and 56% female respondents. Research shows that family social support is most strongly associated with adolescent resilience. This means that the social support provided by the family has a very significant impact on improving the ability of adolescents when facing problems experienced in their lives as children of international migrant workers. Based on these findings, it is expected that mothers who work as international migrant workers when their children are teenagers, because of the level of resilience in the high category.